Analisis Hubungan Kepemimpinan Dan Budaya Organisasi Dengan Motivasi Kerja Dalam Penerapan Good Governance - Leris Situmeang (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
The purpose of this study is to examine and analyze the relationship of leadership and organizational culture with the implementation of good governance through work motivation in Sitahuis District, Central Tapanuli Regency. The total population and sample of this study were 57 people. Data was collected by using questionnaires and interviews. The method of data analysis in this study used descriptive analysis and path analysis. The results indicate that leadership and organizational culture positively correlate with motivation and implementation of good governance. Implications and suggestions are described in the article.